PELATIHAN AKLIMATISASI BIBIT STROBERI HASIL KULTUR MERISTEM BAGI PETANI STROBERI PANCASARI - R. Dwiyani; K.B. Susrusa; I.A.P. Darmawati; G.N.A.S. Wirya; I.G.A. Gunadi; N.N.A. Mayadewi; H. Yuswanti; K.A. Yuliadhi; T.A. Phabiola; R. Kawuri; Y. Fitriani (Buletin Udayana Mengabdi, 2023)
Abstracts The community service activity entitled "Training for Acclimatization of Strawberry Seeds from Meristem Culture for Pancasari Strawberry Farmers" has been completed. This activity was motivated by the problem of seeds by strawberry farmers in Pancasari, where farmers needed healthy seeds from tissue culture, because through propagation with runners, crop yields decreased drastically due to virus attacks. The solution is the use of seeds from meristem culture. Acclimatization training by farmers is important because removing seeds from culture bottles and then growing them on media ex vitro requires skills and understanding of acclimatization theory. The purpose of this service was to provide strawberry acclimatization skills to farmers, so that farmers can acclimatize themselves to meristem cultured strawberries produced by the Tissue Culture Laboratory of the Faculty of Agriculture Udayana University. This activity was based on the results of strawberry meristem culture research in 2019 funded by the ministry of research technology and higher education Republic of Indonesia through a national competitive grant. The results of the current community service concluded several things as follows: The training participants, especially farmers, have succeeded in carrying out their own acclimatization practice; Strawberry seedlings grown in the highlands (Pancasari) had better vigor than those grown in the lowlands (Denpasar). Keywords: acclimatization, meristem culture, Pancasari, strawberry, virus.